Knowing versus doing: Protective health behavior against COVID-19 in Indonesia - Eliana Chavarría; Farah Diba; Maja E. Marcus; Marthoenis; Anna Reuter; Lisa Rogge; Sebastian Vollmer (Georg-August-Universität Göttingen, Courant Research Centre - Poverty, Equity and Growth (CRC-PEG), 2020)
The COVID-19 pandemic shapes the lives of people around the globe - at the same time, people themselves have the power to shape the pandemic. By employing protective health behavior, such as social distancing, hygiene, mask wearing, and appropriate actions when infected, the population can contribute to alleviating the severity of an outbreak. This may be of particular importance whenever health systems or populations are vulnerable to shocks, as is frequently the case in low- and middle-income settings. Therefore, understanding the underlying drivers of protective health behavior against COVID-19 is urgently needed to shape policy responses. We investigate the individual-level determinants of disease knowledge and behavior in the context of the COVID-19 pandemic in Aceh, Indonesia. We use data from a representative population sample of 40-70-year old's, obtained from telephone interviews between March and May 2020 and face-to-face interviews in 2019. We employ linear probability models that account for a comprehensive set of factors that were previously found to influence knowledge and practice during pandemics. These factors pertain to socioeconomic characteristics, behavioral economic preferences, pandemic knowledge, and informational sources. We find that both knowledge and uptake of protective health behavior are relatively high. Knowledge is the largest explanatory driver of protective health behavior, while socioeconomics and economic preferences are minor determinants. However, knowledge itself is strongly shaped by socioeconomic gradients, being lower in less educated, less wealthy and rural households. Similarly, information sources predict knowledge, and differ significantly by socioeconomic groups.
Keywords: 330; COVID-19; Health Knowledge; Health Behavior; Economic Preferences; Indonesia; South-East Asia